Kardiochirurgia DorosłychWpływ wielkości lewego przedsionka na skuteczność ablacji RF u pacjentów z utrwalonym migotaniem przedsionków poddanych operacji wymiany zastawki mitralnej – obserwacje roczne - Myrdko, Tomasz; Rudziński, Paweł; Śnieżek-Maciejewska, Maria; Piątek, Jacek; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Patients (pts) with mitral valve disease and suffering from atrial fibrillation (AF) always have enlargement of the left atrium (LA). Aim: We estimated the influence of LA size on ablation results after one year. Material and methods: Fifty pts (39 female, 11 male) with mitral valve disease and permanent AF aged 61.9±7.4 years (ranging from 50 to 76 years) underwent mitral valve replacement and left-sided radiofrequency ablation (RF). The left atrial diameter was measured in long axis parasternal view. The patients were divided into three groups according to the size of LA: group A, pts with mild dilated LA (4–5 cm); group B, pts with moderate dilated LA (5 6 cm). Results: After one year we observed sinus rhythm in 62.5% of pts from group A; in 61.5% of pts from group B; and only in 12.5% pts from the last group. Conclusions: 1) mild and moderate enlargement of LA does not affect the efficiency of RF ablation; 2) gross enlargement of LA (>6 cm) is connected more frequently with ineffective ablation (but it was not statistically significant); 3) correct estimation of the influence of LA diameter on ablation results requires a bigger group of pts.